Maxilla-first versus mandible-first in bimaxillary orthognathic surgery: a systematic review - Fricain Margaux; Barthelemi Stephane; Lapeyrie Philippe; Masson Regnault Emmanuel (Journal of Oral Medicine and Oral Surgery, 2025)
Introduction: For the great majority of surgeons, orthognathic bimaxillary surgery requires one jaw to be osteosynthetized before repositioning the second jaw. Sequence of bimaxillary surgery between maxilla-first or mandible-first is source of controversy regarding results accuracy in relation to treatment plan. This systematic review aims to compare bimaxillary surgery occlusal, skeletal results and planning conformity according to surgical sequence. Material and methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Three electronic databases were searched in June 2023. Clinical trials and observational studies on patients who underwent bimaxillary surgery as part of orthodontic treatment were included. Inclusion eligibility screening, data extraction and risk of bias assessment were performed independently in duplicate. Results: Eight articles were included. There was no consensus in the accuracy of the results in transversal, sagittal or vertical dimensions. Some clinical conditions seemed to be more suitable for one or other of surgical sequences. Conclusion: This review enabled to propose decision criteria for most appropriate sequence depending on clinical conditions in orthognathic. Given the moderate risk of bias of the majority of included studies, careful data interpretation is needed and future studies of higher quality are recommended.